Perancangan Sistem Presensi Wajah (SIWAJA) Berbasis Internet of Things dengan Notifikasi Telegram - Muhammad Bagas Adi Pangestu; Nuroji, Nuroji (LPPM Universitas Mulia, 2025)
Manual student attendance administration is prone to human error, inefficient, and hinders communication between schools and parents. This study aims to develop the Face Presence System (SIWAJA), an innovative solution integrating face recognition technology and the Internet of Things (IoT) to provide live attendance notifications to parents via Telegram. A key technological advantage of this system is the implementation of the YOLOv8 algorithm, which is emphasized for its high precision in face detection. The development method used is the prototype model, which includes stages of requirements identification, design, implementation, and evaluation. The system was built using an Orange Pi 5 Pro, the Python programming language with the OpenCV library, and the YOLOv8 algorithm for face detection. The research results show that the SIWAJA system was successfully developed and functions as expected, where the IoT-based design supports potential scalability for broader implementation. Black Box Testing validated all main functionalities, from presence-taking to notification delivery. The face detection model showed highly reliable performance with a precision (P) value of 0.97, recall (R) of 0.99, and mAP@.5 of 0.99. In conclusion, SIWAJA proves to be an effective and accurate solution for modernizing student attendance management and enhancing real-time parental involvement, offering significant contributions to the application of IoT in education.